Spiritual well-being and its association with health-related quality of life in primary brain tumor patients. Issue 3 (17th February 2021) - Randazzo, Dina M; McSherry, Frances; Herndon, James E; Affronti, Mary L; Lipp, Eric S; Miller, Elizabeth S; Woodring, Sarah; Healy, Patrick; Jackman, Jennifer; Crouch, Brian; Desjardins, Annick; Ashley, David M; et al.
Abstract: Background: Spirituality can impact patients' attitudes and decisions about treatment and end-of-life care when coping with cancer. Previous studies documented health-related quality of life (HRQoL) and spiritual well-being (SWB) as positively correlated within a general cancer patient population, but little is known about their association in the primary brain tumor population. We sought to measure SWB in primary brain tumor patients and evaluate whether it was associated with HRQoL. Methods: Six-hundred and six patients treated at The Preston Robert Tisch Brain Tumor Center at Duke between December 16, 2013 and February 28, 2014 with data in the PRoGREss registry are included in this retrospective analysis. Each patient completed the Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being 12 (FACIT-Sp-12) and -Fatigue (FACIT-F), and the Functional Assessment of Cancer Therapy-General and -Brain (FACT-G and FACT-Br). Results: Mean age was 49.1 years (SD = 13.5 years), male (N = 328, 54.1%), married (N = 404, 66.7%), at least college-educated (N = 381, 62.9%), and diagnosed with a high-grade glioma (N = 412, 68.0%). Multiple regression analyses were performed on both the FACT-G and the FACT-Br using the FACIT-Sp-12 sub-scales of Meaning/Peace and Faith, FACIT-F, belief in God or a higher power, prayer, gender, tumor grade, and Karnofsky Performance Status (KPS) as predictors. We found that greater SWB (measured by FACIT-Sp-12) was associated with better HRQoL (measured by FACT-G and FACT-Br; p < .0001). Conclusion: The association between reported SWB and reported improved HRQoL emphasizes the importance of spirituality in primary brain tumor patients, suggesting SWB must be considered in strategies to improve HRQoL.